Loyalitas Nasabah Bank Aceh Syariah di Kota Medan (Tinjauan terhadap Nasabah di Luar Provinsi Aceh) - Yusniar Yusniar (Al-Fikru)
This study aims to analyze the effect of religiosity, brand image and Islamic brand love on the loyalty of Bank Aceh customers in Medan City. The research sample is the Acehnese people who live in the city of Medan. This research is a type of quantitative research. The sampling technique used is non-probability sampling for the sample of Bank Aceh Syariah customers, and purposive sampling for leaders, managers and marketing. Data collection techniques used are interviews, observation and distributing questionnaires. The results show that the X1 regression coefficient, 0.346 or 34.6%, is positive, which means that if the religiosity variable has increased by 1%, the level of customer loyalty will increase by 0.346. Then the X2 regression coefficient, 0.175 or 17.5% is positive, meaning that if the brand image variable has increased by 1%, the level of customer loyalty of Bank Aceh Medan will increase by 0.175. And the X3 regression coefficient, 0.289 or 28.9% is positive, meaning that if the Islamic brand love variable has increased by 1%, the level of customer loyalty of Bank Aceh Medan City has increased by 0.289.